Achieving Equality for Women in Labour and Employment – A Comparative Study of Colombia and Canada - Hernandez, Lina (Western, 2017)
The primary focus of this thesis is to analyze and compare the legal systems enacted to protect working women in Colombia and Canada. This thesis focuses on: the protection of maternity and parental rights; the principle of equal pay for work of equal value; and discrimination in employment (including harassment). This research argues that the legislative and judicial changes made in each country to protect working women have not led to substantive equality for working women. This thesis also argues that there is a gap between international and national standards, thus a law reform is appropriate and needed in both the Canadian and Colombian legal systems to bridge the gap and achieve equality for women in employment. Overall, this thesis provides a holistic understanding of two different legal systems in two different countries, both State parties to important International Labour Organization (ILO) and United Nations Organization (UN) treaties and with the same international goal of attaining equality for women in employment.